Enkele kritiese opmerkinge oor die kategetiese beoefening binne die Ned Geref Kerk - Breytenbach, H. S. (Verbum et ecclesia, 1991)
Critical remarks on Religious Education in the Dutch Reformed Church A few statistics are mentioned in this article, and conclusions are drawn from them. Then faith-instruction in the Old and New Testaments is discussed. Religious education is first and foremost, the task of the parents, but officially also the task of the congregation. The congregation must learn to make religious education their own responsibility. In the congregation you learn to believe, and faith is stimulated. The author closes with ten critical statements in an attempt to show a way for religious education in the DRC.